Representations of attachment during middle childhood in a sample of children in care in South Africa as determined by two attachment measures. - Douglas, Danielle (My University, 2012)
This study explored the attachment patterns in middle childhood of children in care in the context of South Africa. Two attachment based measures were used, namely: the kinetic family drawing and a story stem narrative task. The kinetic family drawing was scored using the Kaplan and Main (1986) scoring system and the Family Drawing Global Rating Scale (Fury, Carlson & Sroufe, 1997) whilst the narratives were scored using the Attachment Incomplete Story Task (Granot & Mayseless, 2001; Kerns, Abraham, Schlegelmilch & Morgan, 2007). Results found were that the combined attachment classification resulting from the Kaplan and Main (1986) scoring system and the Family Drawing Global Rating Scale (Fury et al., 1997) showed the highest concordance with the Attachment Story Completion Task (Granot & Mayseless, 2001; Kerns et al., 2007). Furthermore the use of the ASCT (Granot & Mayseless, 2001; Kerns et al., 2008) proved the most simple and effective attachment based measure for use in this population. Thus both projective measures provide insight into the children’s present emotional functioning. Overall findings suggested that 69. 60% of the children were classified as having an insecure-avoidant attachment pattern, and 23.70% as ambivalent, and the mental health implications of such are important considerations for a developing country